The effect of emotional experiences in fieldwork: embodied evidence from a visual approach. Issue 2 (15th March 2023) - Wang, Min; Wu, Jiaxian; An, Ning; Lin, Mingliang
ABSTRACT: Emotion has become an important topic in fieldwork courses of higher geography education. This study attempts to provide embodied evidence of the important value of emotional experiences in fieldwork and clarify that the teaching effect produced by fieldwork in a real environment is difficult to achieve in a virtual environment. Using eye-tracking, this study captured the eye movement data of 16 fieldwork participants and 15 nonparticipants gazing upon photographs and analyzed how emotions affect their acquisition of geographic knowledge. The eye-tracking experiment showed that students who participated in fieldwork processed visual information more quickly and had stronger emotional responses than those who did not participate. This article proposes that fieldwork can provide students the opportunity to encounter the environment in a "mind-body-environment" system, thereby constructing the following two different forms of geographic knowledge: characterizable and explicit knowledge and nonrepresentational, implicit, and embodied knowledge. The latter can be realized only via emotional experiences in the field. Therefore, this article claims that although the information age enables students to acquire remote knowledge of geographical environments through multiple channels, training qualified geographers remains inseparable from fieldwork, especially for cultivating cognition, emotions and responsibility for the "living" world..